CRITERIA OF SYNONYM IN ENGLISH AND UZBEK LANGUAGES (Journal of Universal Science Research, 2023)
This article deals with the various aspects of semantic similarity between synonyms in English and Uzbek language, including core meaning, connotation, register, specificity, and idiomatic expressions. It is outlined that a definition of the term “synonym” provides for any objective criterion of similarity or sameness of meaning as far as it is based on the linguistic intuition of the scholars.